Knowledge transfer through consulting : a service provided by BIBB in international vocational education and training - Dybowski, Gisela [Verfasser] (My University, 2007)
The growing challenges facing international cooperation in vocational education and training (VET) are what prompted BIBB (Federal Institute for Vocational Education and Training) five years ago to reposition itself in the field of international VET. The foundations for the Institute's medium-term activities in international VET were agreed in 2001 with the Federal Ministry of Education and Research (BMBF) and laid out in a "Strategy paper on the internationalisation of VET". (BIBB)
Keywords: I 1 Internationale Berufsbildung; I 1.1 Systemberatung; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Wissenstransfer; Beratung; Dienstleistung; Bundesinstitut für Berufsbildung; Berufsbildung; Internationalisierung